Aircraft suitability model applied to a laminar flow control flight experiment. (2016) - Tucker, Aaron A.; Reed, Helen L.; Saric, William S.
When planning a flight experiment, the test team must analyse the suitability of the testbed aircraft. Often, critical design decisions for the test apparatus are made without high-fidelity models of aircraft performance since few testbed aircraft are designed and built for the flight experiment. This study develops a process to adapt rough performance data to determine the suitability of an airplane to operate at a given angle of attack across a wide range of flight conditions within operational limits. The process illustrates the careful balance of factors in the design of a swept wing laminar flow control wing glove. The process also establishes an important flight planning tool that allows the test team to assess the impact of aircraft performance on the flight experiment. Further, the tool can be updated with flight data when available and leveraged as a planning tool to promote safe and efficient flight research.